'Fraught with background': narration, monstration and style in the biblical adaptations of R. Crumb and Chester Brown. Issue 5 (3rd September 2022) - Fraser, Benjamin
ABSTRACT: This article blends insights into the co-presence of images with the recognition that monstration and graphic style have narrative properties (e.g. Groensteen, Miller, Mikkonen, Postema) in an applied reading of two comics adaptations of biblical stories. Erich Auerbach's classic exploration of biblical vs. Homeric prose in his book Mimesis identifies a key distinction that sheds light on how narration operates in Robert Crumb's The Book of Genesis and Chester Brown's Mary Wept Over the Feet of Jesus . Analysis of these two works is carried out with primary reference to Thierry Groensteen's typology of the four modalities of co-presence in comics (synchronic, diachronic, musical and visual). Through close analyses of typical sequences from each biblical adaptation, a distinction can be observed in the way that comics can either work against or reinforce aspects of biblical narration. In the end, while comics as a medium are by their very nature 'fraught with background' in the way that Auerbach suggests of biblical prose, there are many narrative possibilities available to comics artists that can be created through combinations of monstration and style.